Exemplary features of digital tools for agroecology: A global review - Burns, Sessie A.; Dittmer, Kyle M.; Shelton, Sadie W.; Wollenberg, Eva Karoline (2022)
KEY MESSAGES ◼ Few digital tools support agroecology comprehensively, but many have agroecological components. ◼ Features that improved two-way farmer communication, targeting of farmer subgroups, farmer-driven content and use of human intermediaries were exemplary features for social inclusion. ◼ Exemplary features for technical advisory tools included context-specific technical options, use of videos, integration with coaching and hotlines for questions, and two-way communication. ◼ Exemplary features for performance assessment included collaborative definition of indicators with farmers, easy to use spreadsheets (for researchers) and easily digestible quick view reporting such as pie charts.